About Convergence of Knowledge. The Project e-Infrastructures Austria, an interdisciplinary case study - Budroni, Paolo (Septentrio Conference Series, 2014)
>> See video of presentation (19 min.) The Current Situation In January 2014, the kick-off of the funded three-year university-structuring project "e-Infrastructures Austria: Structure and Development of a Repository Infrastructure", for which 22 Austrian Universities, the National Library and two other academic institutions all over in Austria jointly submitted an application for the development of national e-infrastructures for research and academic teaching. The initiative is coordinated by the University of Vienna. The overall objective is the coordinated establishment and development of repository infrastructures throughout Austria. The project is structured in three parallel-running subprojects, which extend into each other thematically and/or build on each other: Sub-project A: Construction of Repositories and Publication Services: Development of know-how and technology transfer to enable repositories (institutional repositories in the narrower sense) at universities as well as to advise and support in the development of local repositories in organizational, technical, legal and content-based issues. Sub-project B: Design and Construction of Repositories Infrastructures for Research Data, Multimedia, e-Learning Content and other complex data sets Sub-project C: The structure of the knowledge network e-Infrastructures Austria, intended to ensure the convergence of knowledge. This third focus is the development of a competence network for research data and data from research-based courses of study of heterogeneous origins with varying levels of accessibility. Convergence of knowledge The basic ideas behind the network are transparency, communication and a collaborative way of working. The skills and knowledge network are developed on a partnership basis by pooling available expertise and resources, using a trans-disciplinary approach and including many stakeholders (librarians, academics and researchers, IT managers, funding agencies, and so on), which are either within the organization or located outside the institutions. The result is an active exchange of experience in technical, organizational, legal and material respects. The project topics covered include management and organization of repositories, policies, legal & ethical Issues, share and release data, publish data, Open Access, long-term archiving, marketing, training and so on. A consistently significant feature in this context is the anchoring of this content in the organizational structures of libraries and their environments. In the course of the project, individual groups and persons acquire an expertise in very specific areas and can act as contact persons and experts after the project has ended. The know-how is always documented. Results can be translated into practical guidance, surveys, case studies, use cases, best practices, reference lists, reports and so on. It is important that these results be published by the project partners under free licenses and are freely and publicly available. Reference: www.e-infrastructures.at